Comparison of Titanium Dioxide-containing and Titanium Dioxide-free Film Coating Systems - Simon Lawrence; William A James; Sarah Stewart (University of Huddersfield Press, 2023)
Titanium dioxide (TiO2) is an important white pigment and opacifier that has been used in the pharmaceutical industry for over 50 years. It has been included ubiquitously in coloured coating systems and therefore many medicines. Its use in oral solid dosage forms, however, is now under scrutiny due to data linking TiO2 particle inhalation with DNA damage. This also caused the European Union to ban its use as a food additive. Consequently, material suppliers have launched several TiO2-free (TF) pharmaceutical coatings. In this study, two TF coatings based on different pigments were compared with a traditional TiO2-containing coating assessing covering and colour quality. The TF coatings both showed a comparable quality in these parameters to the TiO2-containing coating. The differences in colour and the degree of whiteness were also quantitatively measured and compared using CIELAB measurements derived from optical lens readings. The colour analysing tool used limited this data.